PERAN PMIK DALAM PELAKSANAAN VAKSINASI COVID-19 DI RUMAH SAKIT X BANDUNG - Sisca Nurul Ratnaningrum; Irda Sari (LPSDI Bina Patria, 2022)
The handling of Covid-19 in Indonesia has entered a new phase, namely the existence of the Covid-19 vaccination program. In the implementation of the Covid-19 vaccination, there are still many people who don’t understand the flow of its implementation, so doctors or nurses feel overwhelmed when they are required to become a vaccinator, but on the other hand they are also required to perform data processing. Therefore, PMIK is present as health workers who have been equipped with data processing management competencies, health services and information, to participate in the success of the Covid-19 vaccination program. The purpose of this study was to find out what and how the role of PMIK in the implementation of the Covid-19 vaccination was specifically at Hospital X Bandung. The research method used is qualitative with a descriptive approach. Data collection techniques used are field observations and interviews. The sampling technique used purposive sampling technique with the number of respondents as many as 2 officers in the registration and reporting division. This research was conducted from 5 April – 5 June 2021 at X Hospital Bandung. From the results of the study, it is known that PMIK acts as the person who ensures the flow of the Covid-19 vaccination implementation has met the requirements, complied with government regulations, and the regulations applied at Hospital X Bandung. In addition, PMIK is also a registration, input, recording, and reporting officer. PMIK plays an important role in the implementation of Covid-19 vaccination because PMIK is involved in all stages, starting from site preparation, vaccination process, to reporting. At Hospital X Bandung still using the old groove (using 4 tables). Therefore, it is recommended to implement a simplification of the Covid-19 vaccination flow, so that it is easier to understand, effective and efficient